Effects of direction and gender on lower limb biomechanics during forward lunges in badminton players: a preliminary analysis - Huang, L.; Zhang, Y.; Gao, S.; Lin, J.; Zheng, F.; Gu, Y. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The lunge is a critical movement in badminton, facilitating rapid and efficient court coverage and enabling players to promptly reach the hitting position. While previous studies have examined the influence of lunge direction on lower limb biomechanics, the effects of gender have yet to be explored. Therefore, the purpose of this study was to investigate the combined effects of direction and gender on lower limb biomechanics during forehand and backhand forward lunges in amateur badminton players.